AUTHORSHIP PATTERNS OF LIBRARY AND INFORMATION SCIENTIFIC ARTICLES IN INDONESIA-ACCREDITED JOURNALS - Ayu Wulandari; Bayu Indra Pratama; Muhammad Shobaruddin (Universitas Brawijaya, 2023)
Research on authorship patterns identifies the direction of authorship trends in the field of knowledge. This research aims to determine the authorship patterns in four Indonesian library and information science journals with national accreditation SINTA 2 category from 2013 to 2020. The focus consists of publication, author and affiliate patterns, network, trend, and type of collaboration. To achieve this goal, this study uses a descriptive study with a quantitative approach through bibliometric techniques, especially co-authorship analysis. The study found that the increase and stability of publications were in line with the estasblishment of SINTA 2 accreditation. 66% of authors who published more than one article often wrote collaboratively. The authors who produce the highest articles have published different articles in the four Sinta 2 journals and high academic positions. The authors serve as a center for collaboration. 78% of institutions come from the library and information science. State Universities are the type of institution that produces the highest articles by 73%. Most of the articles in each journal are written by authors affiliated with the journal's managing institutions. Cumulatively, the authorship trend is a collaboration with a degree of 0.56. The trend has changed cumulatively from individual to collaboration since 2016. Most partnerships occur between authors from the same institution, with 73.17%.